2020
DOI: 10.4149/gpb_2020009
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of RFWD3 inhibits cancer cells proliferation and migration in gastric carcinoma

Abstract: The E3 ligase RING finger and WD repeat domain 3 (RFWD3) can stabilize p53 in response to DNA damage, participate in replication checkpoint, and have an important role in multiple myeloma, testicular germ cell tumor and lung carcinogenesis. Its expression and molecular mechanisms have never been explored in gastric cancer. In present study, the RFWD3 was found over-expressed in the both AGS and HGC-27 gastric cancer cells. Knockdown of RFWD3 suppressed cells proliferation activity of gastric cancer cells. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…We have shown here that in HGSOC cells, RFWD3 deficiency can lead to an accumulation of cells in G2/M phase, indicating a potential checkpoint block. This has also been previously reported in gastric cancer cells ( 21 ). A third group have reported a trend towards increased proportion of cells in G2/M phase in the U20S osteosarcoma cell line ( 18 ), however this only achieved statistical significance with one siRNA tested.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We have shown here that in HGSOC cells, RFWD3 deficiency can lead to an accumulation of cells in G2/M phase, indicating a potential checkpoint block. This has also been previously reported in gastric cancer cells ( 21 ). A third group have reported a trend towards increased proportion of cells in G2/M phase in the U20S osteosarcoma cell line ( 18 ), however this only achieved statistical significance with one siRNA tested.…”
Section: Discussionsupporting
confidence: 88%
“…RFWD3 has been previously reported to participate in non-canonical signalling pathways distinct from its role in ICL repair in other cancer types ( 21 , 22 ). Therefore, the effect of RFWD3 deficiency on cancer relevant phenotypes was assessed using the RFWD3 Δ/Δ cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, aberrant activation of UBE2C enhanced cell proliferation, clonogenicity, and invasive growth of NSCLC [ 31 ]. Jia et al reported that RFWD3 was overexpressed in gastric carcinoma, and its knockdown inhibited the proliferation and migration of gastric carcinoma cells through modulating AKT, ERK/P38, and Slug pathways [ 32 ]. In the current research study, we used the mRNA expression data of 71 UbRGs from the TCGA datasets and the LASSO regression analysis to construct a 9-UbRGs predictive signature.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that RFWD3 is an E3 ubiquitin ligase that positively regulates p53 levels in response to DNA damage ( Fu et al, 2010 ). The published literature mentioned that the high expression of RFWD3 was involved in the occurrence and development of gastric carcinoma, and may be an important poor prognostic factor of gastric carcinoma ( Jia et al, 2020 ). Our present study, through IHC analysis and TCGA database, indicated that RFWD3 expression was significantly higher in CRC tissues compared with matched para-tumorous tissues.…”
Section: Discussionmentioning
confidence: 99%